Comparative study of the effect of obesity on lipid profiles levels, insulin resistance and oxidative stress in adolescents - Sundaraveena N.; T. Santhi; Uma T. (International Journal of Medical Research and Review, 2015)
Introduction: Obesity is associated with social and medical risks that especially make it a problem. The study is to determine whether the lipid abnormalities observed in obese adolescents are associated with insulin resistance & oxidative stress.Methods: We evaluated the relationship between lipid levels and insulin resistance and oxidative stress in 30 female obese adolescents who were obese (body mass index > 25 Kg/m). Insulin resistance was assessed by fasting insulin and glucose level, Lipid profile was studied including, total cholesterol, HDL, LDL, and oxidative stress by estimating vitamin-c and Malandialdehyde.Results: All the parameters except serum HDL level showed significant increase in obese adolescents persons while HDL level was significantly decreased.Conclusion: The study indicates elevation of glucose, lipid profile levels and oxidative stress in obese adolescents. This is due to hyperinsulinaemia leads to insulin resistance. Insulin resistance may be responsible, for changes in lipid and lipoprotein concentration. childhood weight requires special early attention because insulin resistance, inflammation and dyslipidemia increase the risk of cardiovascular disease